Development and performance evaluation of sustainable lightweight geopolymer based fireproofing coatings for steel construction - Zhenyu Huang; Yingwu Zhou; Hammad Salahuddin (Sustainable Structures)
This study developed a novel, sustainable, lightweight, and high-ductility fireproofing coating using granulated blast furnace slag (GBFS), fly ash microspheres (FAC), alkali activator, and polyethylene (PE) fiber as raw materials. The critical mixing ratios of FAC to GBFS (4:6), the water-to-binder ratio (0.55), and the alkali activator modulus (1.4) were determined to meet the requirements for fluidity, compressive strength, and flexural strength. The residual strength and thermal stability of the sample were evaluated through high-temperature exposure tests. The compressive strength results showed that even at 900℃, the lightweight geopolymer-based fireproofing coating exhibited 23 MPa as compared to that of 61 MPa at room temperature, which is 30% of its room temperature strength. X-ray diffraction and scanning electron microscopy were carried out to examine the micro-morphology of the samples, revealing that the main component of the geopolymer was Ca2(Al2SiO7) in a colloidal state at 30℃, 300℃, and 600℃. The reduction in strength at this temperature range was mainly attributed to the surface crack extension. However, at 900℃, the gelatinous Ca2(Al2SiO7) underwent dehydration and transformed into crystalline Ca2(Al2SiO7), or zeolite. The interface bond performance between the fireproofing coating and the steel plate was thoroughly tested through direct shear and normal bond tests, using five different bonding techniques, as well as a tensile test on the fire-resistant material coated steel plate. The bond strength from direct shear test ranged from 0.05 MPa to 1.64 MPa and for normal shear test, the strength was in the range of 0.07 MPa to 1.43 MPa. The results of tensile strength test showed that the coating had high ductility and was fire-resistant, and it could deform synergistically with the steel plate, with a maximum tensile strain of 4%. These results demonstrate the coating's excellent deformation performance.